Estratégias de internacionalização das empresas calçadistas brasileiras: uma análise sob as perspectivas da indústria, recursos e instituições - Calixto, Cyntia Vilasboas (Universidade do Vale do Rio dos Sinos, 2013)
The Brazilian footwear industry has decreasing its competitiveness recently mainly due to the emerging of the Asian related industry. Thus, many companies need to find ways to sustain themselves in the market, as well as re-evaluate their positioning. In order to do so, these companies have planned their internationalization embracing this new process. This dissertation intends to analyze the internationalization strategy configuration of different Brazilian footwear companies, based on the analysis of the influence in the industry, on the organizational capabilities and the institutions perspectives. Therefore, this study was directed to comprehend each of the elements of the strategic tripod and its relation to strategy configuration of the footwear industry when seeking overseas markets. It then developed an incorporated case study, interviewing executives of four Brazilian companies. Complementary, five institutions related to the sector were interviewed, in order to widen the knowledge about these entities and how they interact with the industry. With the intention to fulfill the goal of this study, we created an instrument entitled to evaluate the possible influence of the elements of the strategy tripod in the forming of the entrepreneurial strategy. This tool has helped to understand the influence of each of the elements, and the results have demonstrated that the selected categories met empirical verification, in its majority. The study also contributed to the literature on identifying the interaction among the tripod’s elements in the strategic configuration, aspect that was not covered in the original model. This interaction means that the component of one element from the tripod could reflect in other element’s action, suggesting their interaction. During the data analysis, it as verified that some actions could be explained by more than one tripod’s element, depending on the study interest.
Keywords: Institution based view; Strategy; International trade; Visão baseada em instituições; Estratégia; Negócios internacionais; ACCNPQ::Ciências Sociais Aplicadas::Administração